The Factor Affecting Farmer Perceptions of the Implementation of Corporate Farming (Case Study at Tani Maju Sejahtera Cooperative, Malang District, East Java Province) - Matheus Dahoklory; Djoko Koestiono; Hery Toiba (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
This research analyzes the factors that influence farmers' perceptions of the implementation of agricultural corporations in advanced prosperous farmer cooperatives of the Malang district. This study uses binary logistic analysis. The determination of the location is done intentionally considering that the progressive, successful farmer cooperative is a cooperative formed by the government, which has become an experimental agricultural corporation in Purworejo Village, Ngantang District, Malang Regency. A simple random sampling technique selected Ninety-two farmers as respondents in this study. The factors analyzed in this study include the farmer's age, education, number of family dependents, land area, land status, and length of farming. The results showed that the education factor had no significant effect on the implementation of Corporate Farming. In contrast, the characteristics of age, number of family dependents, land area, land status, and length of farming had a significant effect on the opportunities for farmers to join Corporate Farming. Keywords: Farmers, Perceptions, Corporate Farming, Binary Logistic